Patterned growth of β-Ga2O3 thin films for solar-blind deep-ultraviolet photodetectors array and optical imaging application. (10th May 2021) - Xie, Chao; Lu, Xingtong; Liang, Yi; Chen, Huahan; Wang, Li; Wu, Chunyan; Wu, Di; Yang, Wenhua; Luo, Linbao
Graphical abstract: Abstract: Solar-blind deep-ultraviolet (DUV) photodetectors based on Ga2 O3 have attracted great attention due to their potential applications for many military and civil purposes. However, the development of device integration for optoelectronic system applications remains a huge challenge. Herein, we report a facile method for patterned-growth of high-quality β-Ga2 O3 thin films, which are assembled into a photodetectors array comprising 8 × 8 device units. A representative detector exhibits outstanding photoresponse performance, in terms of an ultra-low dark current of ∼0.62 pA, a large I light / I dark ratio exceeding 10 4, a high responsivity of ∼0.72 A W −1 and a decent specific detectivity of ∼4.18 × 10 11 Jones, upon 265 nm DUV illumination. What is more, the DUV/visible (250/400 nm) rejection ratio is as high as 10 3 with a sharp response cut-off wavelength at ∼280 nm. Further optoelectronic analysis reveals that the photodetectors array has good uniformity and repeatability, endowing it the capability to serve as a reliable DUV light image sensor with a decent spatial resolution. These results suggest that the proposed technique offers an effective avenue for patterned growth of β-Ga2 O3 thin films for multifunctional DUV optoelectronic applications.